МЕТОДИКА ВЫЧИСЛЕНИЯ ПРЕДЕЛОВ С ИСПОЛЬЗОВАНИЕМ ЭЛЕМЕНТАРНЫХ ПОДСТАНОВОК И ТЕОРЕМ - Хакимов, А.; Ашурова, Д.; Шокирова, Д. (SCIENCE and SOCIETY, 2025)
The article discusses the simplification of calculating certain non-standard sequences and function limits using linear substitutions, Lemmas, and theorems.
Keywords: limit of a sequence; methods of calculating limits; limit calculation using lemmas; L'Hopital's rule